THE EFFECT OF STAR FRUIT JUICE (Averrhoa bilimbi Linn.) ON TOOTH COLOR CHANGES IN THE TOOTH BLEACHING PROCESS - Rifky, Mirna; Alawiyah, Tuti; Karolina (Moestopo International Review on Social, Humanities, and Sciences, 2025)
Background: Tooth discoloration is an aesthetic problem that motivates patients to seek treatment. Tooth discoloration can be addressed through dental bleaching treatment. Natural ingredients can be used as an alternative to teeth whitening that is safer, more readily available, and more affordable. Bilimbi fruit juice (Averrhoa bilimbi Linn.) contains oxalic acid, which acts as an oxidizing agent capable of breaking down pigments by releasing oxygen in the form of free radicals. The released oxygen then breaks down the complex pigment molecules that cause tooth discoloration into simpler, colorless molecules, resulting in a whitening effect on the teeth. Objective: To determine the effect of color of teeth soaked in bilimbi fruit juice (Averrhoa bilimbi Linn.) on the bleaching process. Methods: This research is an experimental laboratory study with a pre-test post-test design method. The research sample consisted of 27 first and second permanent premolars, both maxillary and mandibular, which were soaked in bilimbi fruit juice (Averrhoa bilimbi Linn.) with a duration of 1 hour, 3 hours and 5 hours. The study was conducted by measuring differences in tooth color after soaking using Vita Easyshade V. Results: All groups of samples produced changes after soaking bilimbi fruit juice (Averrhoa bilimbi Linn.). The value of light, chrome, and hue showed a significant difference in tooth color (sig < 0.05). Conclusion: There are changes in tooth color after being soaked in starfruit juice (Averrhoa bilimbi Linn.) due to its oxalic acid content and influenced by pH, concentration, soaking duration, surface cleanliness of the teeth, shelf life of the material, temperature, sealed environment, and additives. Keywords: Color Change, Bilimbi Fruit Juice (Averrhoa bilimbi Linn.), Bleaching